Seasonal and annual precipitation time series trend analysis in Al-Kabir Al-Shamali river basin, Syria - ديوب, هادي; طاهر شيخو; يوسف العلي (Latakia University Journal -Biological Sciences Series, 2023)
Climate change due to human activities is one of the major challenges facing human development in the twenty-first century. In this study, trend of annual and seasonal precipitation was identified in Al-Kabir Al-Shamali river catchment, northwest of Syria, using the monthly precipitation values ​​four for meteorological stations (Bouqa, Al-Haffa, Aen Aido, Kassab) distributed in the catchment and for a period extending from 1960 to 2010. Linear regression analysis using the ordinary least squares method (OLS) was used to determine the precipitation trend and magnitude of change in the studied precipitation series. The results revealed a clear and significant downward trend in annual precipitation in all stations, greater than 30%, resulting from a sharp drop in precipitation amounts for the winter and spring seasons in particular. The results of the study can be useful for water resources management and sustainable agricultural planning in the basin.